Are Business Savings a Mediator for Culinary Tourism Development? - Sumastuti, Efriyani; Amelia, Dhea Rizky; Indriasari, Ika (Economics Development Analysis Journal, 2024)
Culinary tourism significantly boosts local economies and enriches tourist experiences. This study investigates whether business savings mediate the relationship between financial literacy, profit, and culinary tourism development in Klaten, Central Java, Indonesia. Employing a quantitative approach with a case study design, the research involved 100 culinary business owners as respondents. Data were collected through questionnaires and interviews and analyzed using path analysis with SmartPLS 3.0. The findings reveal that financial literacy and profit influence business savings and culinary tourism development. Furthermore, business savings mediate the relationship between financial literacy, profit, and culinary tourism development. Specifically, higher financial literacy and profits lead to increased business savings, which then facilitate investment in infrastructure, innovation, marketing, and employee training, thereby enhancing the overall development of culinary tourism. These results provide a comprehensive understanding of the financial dynamics driving culinary tourism growth in Klaten. The study's implications include recommendations for policymakers, business owners, and financial institutions to design effective strategies and policies that support the sustainable growth of the culinary tourism sector.